The implications and effect of the General Laws (Anti-Money Laundering and Combating Terrorism Financing) Amendment Act 22 of 2022, on the Trust Property Control Act 57 of 1988 - Van der Linde, Anton (University of Pretoria, 2025)
Mini Dissertation (LLM (Private Law) Estate Law))--University of Pretoria, 2024.